Factors influencing the adoption of mobile services consumers' preferences using analytic hierarchy process - Shahrokh Nikou; Jozsef Mezei; Harry Bouwman; Yong Liu (International Telecommunications Society (ITS), 2011)
The rapid and widespread development of innovations in mobile services is changing societies and improving lives around the world. Due to lagging adoption, many of these new innovations have yet failed to generate revenue that was expected by mobile network operators, application and content developers. There are several factors which are affecting the service adoption by consumers. This paper aims to provide practitioners and academics, an insight on what consumers' preferences are by using an Analytic Hierarchy Approach (AHP). The objective of this paper is to identify factors influencing the adoption of the mobile services. In this study we have considered Payment Mode, Functionality, Added Value and PQCP (perceived quality, cost and performance) as the main service adoption factors. The survey results indicate that Functionality is the most important influencing factor for the respondents, followed by Added Value, PQCP and Payment Mode.
Keywords: 330; Adoption; AHP; Mobile Value Services; Consumer's Preferences